Synthesis and Characterization of Linear Copolymers Based on Pharmaceutically Functionalized Monomeric Choline Ionic Liquid for Delivery of p-Aminosalicylate - Shadi Keihankhadiv; Dorota Neugebauer (Pharmaceutics, 2023)
Bioactive linear poly(ionic liquid)s (PIL) were designed as carriers in drug delivery systems (DDS). Their synthesis was based on a monomeric ionic liquid (MIL) with a relevant pharmaceutical anion to create therapeutically functionalized monomers, which further can be used in the controlled atom transfer radical polymerization (ATRP). The presence of chloride counterions in the quaternary ammonium groups of choline MIL, e.g., [2-(methacryloyloxy)ethyl]trimethyl-ammonium chloride (ChMACl), was stimulated to undergo the anion exchange with p-aminosalicylate sodium salt (NaPAS) as the source of the pharmaceutical anion with antibacterial activity. The resultant [2-(methacryloyloxy)ethyl]trimethylammonium p-aminosalicylate (ChMAPAS) was copolymerized to attain the well-defined linear choline-based copolymers with various contents of PAS anions (24–42%), which were regulated by the initial ratio of ChMAPAS to MMA and conversion degree. The length of polymeric chains was evaluated by the total monomer conversion (31–66%) yielding degree of polymerization (DPn = 133–272). Depending on the polymer carrier composition, PAS anions were exchanged by 60–100% within 1 h, 80–100% within 4 h, and completely after 24 h by phosphate anions in PBS imitating a physiological fluid.